2016
DOI: 10.1111/jns.12180
|View full text |Cite
|
Sign up to set email alerts
|

Transthyretin familial amyloid polyneuropathy (TTR‐FAP) in Mallorca: a comparison between late‐ and early‐onset disease

Abstract: The age of onset (AO) of hereditary ATTR amyloidosis (hATTR) is known to vary between populations, with differing characteristics reported according to AO in endemic/non‐endemic foci. This was a retrospective study of patients with early AO (<50 years) and late AO (≥50 years) hATTR at our center in Mallorca. Data were collected on patient demographics, clinical disease manifestation, and physical symptoms. A total of 95 patients were analyzed, with mean follow‐up of 9 years from diagnosis. The early AO group i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
(33 reference statements)
1
6
0
Order By: Relevance
“…The results of our study largely confirm a number of essential findings from previous studies conducted in other countries: Late-onset ATTRv-PN was found to be more difficult to diagnose and to be associated with higher neurologic disease severity and frequent cardiac involvement [19,21,27]. Muscle weakness and impairment of gait, both clinical indicators of advanced polyneuropathy, were also frequently met in our patient cohort.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The results of our study largely confirm a number of essential findings from previous studies conducted in other countries: Late-onset ATTRv-PN was found to be more difficult to diagnose and to be associated with higher neurologic disease severity and frequent cardiac involvement [19,21,27]. Muscle weakness and impairment of gait, both clinical indicators of advanced polyneuropathy, were also frequently met in our patient cohort.…”
Section: Discussionsupporting
confidence: 89%
“…However, most prospective studies on tafamidis have focussed on cohorts in endemic ATTRv-PN hotspots such as Portugal or Brazil recruiting mostly younger patients at early stages of the disease [11,12,18,19]. Meanwhile, patient cohorts in other parts of the world presenting with different genotypes and phenotypes are still underrepresented in the current literature [13,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Val30Met (V30M) mutation is the most common mutation in the transthyretin gene worldwide, and the classical V30M ATTRv-PN phenotype is of a small-fiber predominant neuropathy with onset in third or fourth decade [1]. A late-onset form of V30M ATTRv-PN in which symptoms manifest in the sixth decade or later has been reported in several countries, and seems to be the most common form outside endemic regions [2][3][4][5][6]. Late-onset V30M ATTRv-PN affects both large and small sensory fibers and has few autonomic symptoms and more severe motor and cardiac involvement than earlyonset disease [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Variation in AO between clusters and within the same focus has already been described [15][16][17]. Additionally, mean age at onset (AO) varies between geographical areas such as Portugal, Japan, Sweden, Majorca and Brazil, although the range is similar: 19-82 in Portugal [18], 23-79 in Majorca [19]. Among Portuguese families, an increasing number of late-onset cases (!50 years) have been observed and asymptomatic carriers aged up to 95 years have been identified [16].…”
Section: Introductionmentioning
confidence: 91%